In vitro effectiveness of different dental bleaching protocols using violet LED - Bachiega-Silva, Bruno; Mayer-Santos, Eric; Jurema, Ana Luiza Barbosa [UNESP]; Caneppele, Taciana Marco Ferraz [UNESP]; Brugnera-Junior, Aldo; de Freitas, Patrícia Moreira (Elsevier, 2023)
Purpose: There has been growing demand for dental bleaching worldwide, however, despite being effective, hydrogen peroxide (HP) can negatively affect the dental structure. Thus, new techniques, such as violet LED light have emerged and need to be studied. The aim of this study was to analyze and compare the effectiveness of violet LED light alone or combined with 35% HP gel. Methods: Six different tooth bleaching techniques (n = 10) were performed in intrinsically pigmented bovine teeth: G1 - 35% HP (1x/week for 4 weeks, 45 min of gel application); G2 - 35% HP (1x/week for 4 weeks, 15 min of gel application); G3 - violet LED (1x/week for 4 weeks); G4 - violet LED (2x/week for 2 weeks); G5 - violet LED (4x/week for 1 week); G6 - Violet LED + 35% HP (hybrid technique, 1x/week for 4 weeks, 15 min of gel application). Specimens were submitted to color evaluation at predetermined times using Konica Minolta® spectrophotometer, and the surface morphology (n = 3) was qualitatively analyzed by Scanning Electron Microscope (SEM). Data of the color change test were analyzed considering a 5% level of significance. Results: There was significant difference in color (p <0.05) for all groups after bleaching protocols. SEM analysis revealed that the greatest change in surface occurred in Group G1, with demineralization of the dental enamel. When considering the same time interval, there were no statistical differences for axis L*, but differences were shown for axis a* (G2, G3, G4 ≥ G1, G5 ≥ G6) and b* (G1, G2, G3, G4, G5 > G6). Regarding the comparison of ΔE00 between groups, results showed statistical difference between groups, with G1 ≥ G2, G5, G6 ≥ G3, G4. Conclusion: Bleaching protocols with less time (15 min) or no exposure to 35% HP (violet LED, 4x/week) could promote bleaching results as those obtained by the conventional technique using 35% HP for 45 min, with no enamel surface changes, showing to be a promising alternative to tooth bleaching.
Keywords: Color; Dental bleaching; Hydrogen peroxide; SEM; Violet LED